Pattern of Health Problems among Tea Garden Workers of Malnicherra Tea Estate in Sylhet District of Bangladesh - Dip, Rashidul Islam; Hossain, Anwar; Rahman, Md. Abdur; Mahbub, Afsana; Nipu, Shaon Akter; Mostofa, Fatima Binte; Rahman, Md. Ashiqur; Akram, Arifa (Bangladesh Journal of Infectious Diseases, 2026)
Background: Tea plantation workers form an important but underrepresented minority in Bangladesh, often exposed to occupational hazards, poor living conditions and limited access to healthcare. Objectives: This study was aimed to assess the pattern of health problems and associated socio-demographic and occupational factors among tea workers in Malnicherra Tea Estate, Sylhet. Methodology: This descriptive cross-sectional study was conducted using a semi-structured questionnaire covering socio-demographic data, occupational information and health status. Data were collected from 150 respondents selected through convenient sampling. Results: The findings revealed that the majority of workers were female 102 (68%) and 81(54.0%) were aged between 25 to 45 years. A total of 105(70.0%) of households income ≤15,000 BDT/month and 96(64.0%) lived in kutcha houses, reflecting poor living conditions among their community. The most commonly found health problems were musculoskeletal pain 87 (58.0%), skin diseases 62(41.0%), respiratory symptoms 51(34.0%) and gastrointestinal problems 44 (29.0%). About onethird 48 (32.0%) of workers reported having chronic diseases such as hypertension and asthma. Regarding healthcare-seeking behavior, more than half 80(53.0%) were dependent on tea garden clinics, followed by traditional healers 31(21.0%) and government hospitals 22(15.0%). Preventive health practices were sufficient, with 108(72.0%) using safe water and 98(65.0%) using sanitary latrines, though only 57(38.0%) had received health education and 83(55.0%) reported being vaccinated under the EPI program. Chi-square analysis revealed significant associations between gender and specific illnesses. Conclusion: The study concludes that tea workers face significant occupational and health-related challenges linked to poverty, poor working conditions and limited health awareness. Improving access to healthcare, occupational safety and health education is essential to promote their health and well-being. Bangladesh Journal of Infectious Diseases, December 2025;12(2):267-272